Metaphors in Arbitral Awards - Ornella Guarino (Iperstoria)
This article investigates the use of metaphors in arbitral awards, examining how these figurative expressions become embedded in legal reasoning and shape decision-making. Drawing on the pervasive role of metaphors in everyday language (Lakoff and Johnson 1980, 3; Semino 2008, 1) and legal discourse (Winter 1989, 1222), the study acknowledges the influence of legal traditions on linguistic choices in arbitration texts (Gotti 2008, 232). It situates its analysis within the broader framework of genre theory, emphasizing the intrinsic link between legal discourse and its institutional and professional contexts (Bhatia, Garzone and Degano 2012, 1; Fairclough and Wodak 1997, 276).